2008
DOI: 10.1186/1471-2407-8-361
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of PROSPECT-CONKO 004: a prospective, randomized trial of simultaneous pancreatic cancer treatment with enoxaparin and chemotherapy)

Abstract: Background: Advanced pancreatic cancer, in addition to its high mortality, is characterized by one of the highest rates of venous thromboembolic events (VTE) as compared to other types of cancer. Enoxaparin, a low molecular weight heparin (LMWH), has proven to be effective for the prevention and treatment of VTE in surgical and general medical patients. Results of some small studies suggest that this benefit might extend to patients with cancer, however, enoxaparin is not currently indicated for this use. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…However, the risk of thromboembolism among patients in our cohort receiving NCT (19%) was much higher than the baseline risk of the untreated patients in these studies (3.9% and 3.4%, respectively), suggesting that prophylaxis may yield a larger benefit in patients with urothelial carcinoma. This suggestion is supported by 2 randomized studies in patients with pancreatic cancer, whose baseline risk of VTE is similar to the risk reported in our study, which showed absolute risk reductions of 9.5% and 19.6% with enoxaparin and dalteparin prophylaxis, respectively [24,25]. Furthermore, an incidence of 19% is higher than the baseline risk of VTE in many groups in which VTE prophylaxis is recommended by the American College of Chest Physicians, including surgical patients without cancer [26].…”
Section: Discussionsupporting
confidence: 89%
“…However, the risk of thromboembolism among patients in our cohort receiving NCT (19%) was much higher than the baseline risk of the untreated patients in these studies (3.9% and 3.4%, respectively), suggesting that prophylaxis may yield a larger benefit in patients with urothelial carcinoma. This suggestion is supported by 2 randomized studies in patients with pancreatic cancer, whose baseline risk of VTE is similar to the risk reported in our study, which showed absolute risk reductions of 9.5% and 19.6% with enoxaparin and dalteparin prophylaxis, respectively [24,25]. Furthermore, an incidence of 19% is higher than the baseline risk of VTE in many groups in which VTE prophylaxis is recommended by the American College of Chest Physicians, including surgical patients without cancer [26].…”
Section: Discussionsupporting
confidence: 89%
“…Despite the relatively low incidence of vte in the control arm (3.4%), the study demonstrated a significant reduction in the incidence of vte in patients receiving semuloparin (1.2%), with no apparent increase in the incidence of major bleeding 60 . Similarly, the fragem and conko 004 trials explored thromboprophylaxis in patients with locally advanced pancreatic cancer undergoing systemic chemotherapy and demonstrated a combined vte risk reduction of 12.5% 61,62 .…”
Section: Thromboprophylaxis In Ambulatory Patients With Cancermentioning
confidence: 99%
“…When the dose of S-NACH was increased to 20 mg/kg, there was still no difference in mean bleeding time. Further, clinical studies have demonstrated that prolonged administration of heparin derivatives can result in improved survival in certain patient populations but with risk of bleeding [33,34]. …”
Section: Discussionmentioning
confidence: 99%